The Oxford India Hinduism reader - Dalmia, Vasudha, 1947-; Stietencron, Heinrich von. (New Delhi : Oxford University Press, 2009)
Contributed articles orginally presented at symposia in 1990 and 1997.
Originally published: 2007.
Includes bibliographical references.
Keywords: Hinduism -- Congresses; Hinduism and state -- Congresses; Hinduism and politics -- Congresses